Mental disorders and subsequent suicide events in a representative community population - Adhikari, Kamala (J Affect Disord, 2020)
OBJECTIVE: : This study examined the patterns of association between mental disorders and subsequent suicide in a community sample representative of the Canadian household population. METHODS: : This retrospective cohort study used data from the Canadian Community Health Survey 2002 linked to the Death Database 2000-2011 and the Hospitalization Database 1999/2000-2012/2013) (n=27,000). Mental disorders (past year major depressive episodes (MDE), bipolar disorders (BPD), anxiety disorders (AD), and substance dependence (SD)) and subsequent suicide events (deaths or hospitalizations for suicide attempts) were identified. Competing risk regression models were used to analyze the time-to-event data, adjusting for age, sex, marital status, and educational attainment. RESULTS: : Past year mental disorders were diagnosed in 11.38% of the cohort and 0.41% had suicide events. An increased hazard of suicide events associated with MDE, SD and AD weakened over-time, but this was not observed for BPD. For example, the HR of suicide events for MDE was 6.02 (95% confidence interval (CI)=2.65, 13.68) in the first 4 years, whereas, it was 2.03 (95% CI=0.91, 4.53) after 4 years. Whereas, the HRs of suicide events for BPD were 16.95 (95% CI=6.88, 41.75) and 15.81 (95% CI=5.89, 42.45) before and after 4 years. LIMITATIONS: : Diagnostic data are likely to underestimate the prevalence of suicide events. CONCLUSIONS: : The risk of suicide events declined over time for MDE, SA and AD, but remained high for BPD. This may reflect improvement over time in MDE, SA and AD, but indicates that people living with BPD have a persistent elevated hazard of suicide events.